2008
DOI: 10.1071/wf07038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water and terpenes on flammability in some dominant Mediterranean species

Abstract: Abstract. In the Mediterranean basin, fires are a major concern for forest and shrubland ecosystems. We studied flammability, its seasonality and its relationship with leaf moisture and volatile terpene content and emission in the dominant species of a Mediterranean shrubland and forest in Catalonia (NE Iberian Peninsula). We measured temperatures and time elapsed between the three flammability phases: smoke, pyrolysis and flame, for four seasons. We sampled twice in spring because of an occasional drought per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 15 publications
(25 reference statements)
8
81
2
6
Order By: Relevance
“…Given that water use strategies control the quantity of water maintained inside plant cells under drought conditions in order to withstand drought, the two groups of plant species mentioned above may have distinct flammability behaviours, since the amount of heat required to evaporate water is positively correlated with MC [38]. Moreover, Alessio et al [35] and White and Zipperer [1] confirmed this fact by indicating that flammability was strictly related to MC due to physical and chemical mechanisms as well as physiological elements, especially whether the character is deciduous or evergreen as this can influence the plant flammability [1]. Indeed, the species examined in this paper are subdivided into drought-deciduous and evergreen sclerophyllous species.…”
Section: Fi Behaviour and Flammability Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that water use strategies control the quantity of water maintained inside plant cells under drought conditions in order to withstand drought, the two groups of plant species mentioned above may have distinct flammability behaviours, since the amount of heat required to evaporate water is positively correlated with MC [38]. Moreover, Alessio et al [35] and White and Zipperer [1] confirmed this fact by indicating that flammability was strictly related to MC due to physical and chemical mechanisms as well as physiological elements, especially whether the character is deciduous or evergreen as this can influence the plant flammability [1]. Indeed, the species examined in this paper are subdivided into drought-deciduous and evergreen sclerophyllous species.…”
Section: Fi Behaviour and Flammability Classificationmentioning
confidence: 99%
“…Indeed, MC has a profound effect on different aspects of flammability [1,[35][36][37]49], especially TI [5,15,38] and flame characteristics [15,36]. Behm et al [39] considered MC as an indicator of ignitability inter alia.…”
Section: Flammability Index Vs Moisture Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in Mediterranean trees (e.g., Pinaceae and Cupressaceae) the abundance of organic oils and organic volatile compounds and terpenes, whose flash points are low, largely contributes to the ignition and spread of fire (Alessio et al 2008); at the same time, the susceptibility to burn of any given fuel is manifested only under particular weather conditions, as it is largely dependent on fuel moisture content.…”
Section: Introductionmentioning
confidence: 99%